Scale effect of storm sewage overflow structure - S. Y. Lim ,; K. H. M. Ali, (1990)
This paper describes an investigation into the scale effect of model sizes on the particle retention efficiency of the stilling pond type storm sewage overflows. The scaling criteria for model-prototype similarity were examined. Data from previous studies on scale effect were reviewed and analysed and their shortcomings discussed. A qualitative comparison of the present model results with the prototype data obtained by Saul (1977) were presented and confirmed the findings that an increase in model size resulted in a decrease in the efficiency of a chamber